Novel Development of Parafoveal Capillary Density Deviation Mapping using an Age-Group and Eccentricity Matched Normative OCT Angiography Database - Andrade Romo, Jorge S. (Transl Vis Sci Technol, 2019)
PURPOSE: We evaluate the impact of age and signal strength index (SSI) on foveal avascular zone (FAZ) metrics and parafoveal capillary density measured using optical coherence tomography angiography (OCT-A), and propose a deviation mapping approach that accounts for age-group, SSI, eccentricity, and variation in FAZ size. METHODS: Parafoveal OCT-A with full vascular layer was obtained for 261 controls and four patients with retinal abnormalities. Parafoveal capillary densities were measured within eight consecutive 200-μm wide annuli from the FAZ border. In controls, the impacts of age and SSI on FAZ metrics and parafoveal capillary density were evaluated. Deviation maps highlighting regions with density at the lower and upper tails of the age-group and eccentricity matched distribution were generated. RESULTS: Linear regressions showed significant correlations between age, SSI, and mean parafoveal capillary density. There was a significant difference in FAZ metrics and parafoveal capillary densities with different age groups after controlling for SSI using univariate analysis. However, the effect of age on parafoveal capillary density disappeared after controlling for SSI using multivariate linear regression analysis. Our deviation mapping approach was able to identify regions with abnormal density in four patients. CONCLUSIONS: Our findings suggest that the relationship between parafoveal capillary density and age is confounded by SSI. Parafoveal capillary density is SSI- and eccentricity-dependent. An age-group and eccentricity matched normative database was used as the basis for a parafoveal capillary density deviation mapping technique, providing an intuitive way to assess the status of parafoveal capillary density in individual eyes. TRANSLATIONAL RELEVANCE: Understanding the impact of age and SSI on parafoveal capillary density is critical for providing accurate interpretation of OCT-A. We demonstrate an age-group and eccentricity matched deviation mapping technique for an intuitive assessment of retinal regions with abnormal density.